The Relationship Between Agility and Speed on Dribbling Ability in Futsal Extracurricular Players at SMPN 13 Seluma - Dodo, Iduar; Personi, Megi; Astuty, Lina Try (Journal of Physical Education and Sports, 2026)
This study aims to determine whether there is a relationship between agility and speed on dribbling ability in extracurricular futsal players of SMP 13 Seluma. This type of research is correlation with test method with a sample of 18 players. The results of the study show a positive relationship between agility and dribbling of extracurricular players of SMP 13 Seluma with tcount = 2.2961 at α = 0.05, while ttable = 1.7010. The contribution is 52.72%. There is a negative relationship between speed and dribbling of extracurricular players of SMP 13 Seluma with tcount = 0.7580 at α = 0.05, while ttable = 1.7010. The contribution is 5.74%. There is a positive relationship between agility and speed with dribbling the ball of extracurricular players of SMPN 13 Seluma with the significance of the r count test = 0.3670 at α = 0.05. r count = 0.3987 > r table 0.3670. Its contribution is 15.89%.